The effect of using resource consumption accounting in improving the quality of accounting information: An exploratory study in the general company of textile industries, wasit (Entrepreneurship Journal for Finance and Business, 2021)
The research aims to clarify impact of using resource consumption accounting to improve the quality of accounting information that management needs it for making future decisions that related to cost management and resources and the rate of its exploitation. In the section, the researcher dealt with the concept of resource consumption accounting, get to know its steps, and the benefits of using it. As for the second section, he touched on the quality of accounting information and their characteristics, and standards for measuring the quality of information. The researcher adopted use of the analytical and statistical aspect to verify the research hypothesis through using a questionnaire that was distributed to a group of people consisting of administrators, accountants, engineers, technicians and a group of academics. The researcher concluded that resource consumption accounting helps in providing useful information for decision-making that includes the company's resources and the relationship between these resources, thus it achieves the quality of the information. The researcher made important recommendations, as he recommends the adoption of resources consumption accounting which it provides useful information to decision-makers that help them in planning and managing resources in the future